2019
DOI: 10.1002/jmv.25388
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies against BKPyV subtype I and IV in kidney transplant recipients and in the general Czech population

Abstract: Active infection with BK polyomavirus (BKPyV) may cause serious complications in transplantation settings. Recently, the level of BKPyV IgG seroreactivity in graft donors has been shown to predict viremia and BKPyV‐associated nephropathy in kidney transplant (KTx) recipients. Pretransplantation testing of the donor and recipient BKPyV serostatus could, therefore, identify patients at high risk. For the development of serological immunoassays, antibody response to the predominant BKPyV subtypes (BKPyV‐I and BKP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…17,18 Higher titer of anti-BKPyV IgG in the donor and its lower titer in the recipient increase the probability of early BKPyV viremia. 19,20 We believe that with a high prevalence of BKPyV infection in the population, where more than 90% of adults become seropositive by the end of their twenty-third year, 21 we can expect similar anti-BKPyV antibodies distribution in our monitored groups.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…17,18 Higher titer of anti-BKPyV IgG in the donor and its lower titer in the recipient increase the probability of early BKPyV viremia. 19,20 We believe that with a high prevalence of BKPyV infection in the population, where more than 90% of adults become seropositive by the end of their twenty-third year, 21 we can expect similar anti-BKPyV antibodies distribution in our monitored groups.…”
Section: Discussionmentioning
confidence: 75%
“…Not only donor serostatus but also different BKPyV specific antibody titers, which may reflect current BKPyV replication, affect the risk of BKPyV viremia and viruria in renal recipients 17,18 . Higher titer of anti‐BKPyV IgG in the donor and its lower titer in the recipient increase the probability of early BKPyV viremia 19,20 . We believe that with a high prevalence of BKPyV infection in the population, where more than 90% of adults become seropositive by the end of their twenty‐third year, 21 we can expect similar anti‐BKPyV antibodies distribution in our monitored groups.…”
Section: Discussionmentioning
confidence: 99%
“…Flower et al reported elevated BK specific IgM antibody levels that persisted for a long duration in post-transplantation adult KTR, compared to healthy controls [ 27 ]. On the other hand, Hejtmánková et al showed lower seroconversion rates following BK virus infection in KTR, compared to healthy controls (38% vs. 52%) [ 28 ]. Hence, it is difficult to discern whether the serologic response of our cohort to COVID-19 infection is comparable to responses of other common viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…The polyprotein strategy is employed by positive RNA viruses, including retroviruses such as HIV (Human Immunodeficiency Virus) [ 17 ]; coronaviruses such as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) [ 20 ]; and by some DNA viruses, e.g., poxviruses (smallpox virus) [ 21 ] or herpesviruses [ 22 ]. Other DNA viruses, such as polyomaviruses [ 23 , 24 ], all negative RNA viruses (among them, influenza virus [ 25 ]), and double-stranded RNA viruses [ 26 ] use different strategies of protein expression and encode no protease.…”
Section: Precursors As Major Signalization and Orchestration Agentsmentioning
confidence: 99%